A study of AERMOD tiering approach for prediction of nitrogen dioxide in Maptaphut industrial area, Thailand - S. Tunlathorntham (2018)
© 2015 Taylor & Francis Group, London. The AERMOD air dispersion modeling system was applied to predict the dispersion of nitrogen dioxide (NO2) in Maptaphut industrial area, Thailand. In this paper, data from 292 point sources were used as input data. Modeled results were validated with measured data, obtained from 10 receptor sites on an hourly basis. The Tier 1 approach (100% conversion of NOx to NO2) resulted to the highest predictions of NO2 concentrations. Overall predicted results, obtained from tier 3 were less bias with those measured results as compared with other tier. Therefore, tier 3 may be considered as appropriate calculation for prediction of annual average concentration. However, as for conservative purpose, tier 1 is the best choice to determine the maximum ground level concentration of NO2 in this paper.